Urinary proteomics in kidney and cardiovascular disease - Mischak, Harald (Henry Stewart Talks, 2013)
Omics technologies, Technology platforms: (2DE-MS, LC-MS-MS, CE/MS), Clinical proteomics, Precision as a function of no. of markers, Human urinary LMW proteome database, Requirements for biomarker selection, How to identify valid proteomic biomarkers, Effect size estimation and the number of samples, Erroneous biomarkers, Classification using different sizes of training sets, Classification errors, CKD biomarkers, Biomarker validation, Pathophysiological suggestions, Selected urinary peptides and CKD staging, Multicentric European PRIORITY trial, Proteomics of coronary artery disease and of diabetic nephropathy